Lighthouse - Smart Virtual Learning Platform - Abeyrathne, P.K.R.R.I.; Sarathchandra, B.R.I.D.; Hewavitharana, D.T.R.; Perera, L.M.D.; Wijesundara, M.N. (2018 National Information Technology Conference (NITC), 2018)
This paper presents the design, development and performance evaluation of a new virtual learning platform. The novel features in this platform include real-time transcribing of live lectures conducted in English and the ability to search recorded lectures based on keywords mentioned during the lectures. This is in addition to real-time streaming and archiving of nine channels of information namely; audio, subtitles, video, slide synchronization, code editor, whiteboard, chat, polls and emotion. The system provides a number of novel features to ease the lecturer's workload. These include one touch recording, real-time polling, real-time emotion detection of students, and cloud based lecture editor allowing editing of each of the nine channels. From an operational perspective, the system requires no additional or special hardware other than a laptop, and it uses cloud based streaming and storage, eliminating the need for a dedicated infrastructure.